KRITIK TERHADAP MODEL PERTANIAN KONTRAK PERUSAHAAN JICA DAN TAIWAN ICDF BERDASARKAN PERSPEKTIF PETANI - Nindya Kalisha Putri; Adi Nugraha (Universitas Galuh Ciamis, 2020)
Contract farming is considered as the starting point for a partnership between companies or agencies and small farmers. Contract farming aims at mutually benefiting contract actors. However, when realizing the contract, there are points in the contract that can not be fully implemented in a long enough period so that farmers feel the contract is not as expected. The purpose of this study is to criticize the contract farming model that is carried out in the hopes of farmers and create an ideal model based on these criticisms. This study uses a qualitative research design with a case study approach. The results of this study indicate that less optimal contact was carried out in the marketing department when compared to contracts that had previously been agreed by both parties. Differences in the characteristics of farmers with systems running on modern markets and differences in payment systems that run with markets are the cause of these problems. Expanding the market according to the characteristics of farmers and enforcing the system by what was agreed with the third parties involved in the contract are noteworthy so that the contract is by the expectations of both parties.